Hydrothermal synthesis of vanadium dioxide nanoparticles and its applications - Liu, Guowei (Nanyang Technological University, 2021)
Vanadium dioxide (VO2), as the typical phase transition material, has drawn an intensive study including the fabrication, stimuli to trigger the transition as well as the high-performance devices based on VO2 with different applications. High-performance optical and electrical applications of VO2 require the synthesis of the VO2 nanoparticles (NPs)with pure phase, high crystallinity, as well as controlled morphology and facet. However, because the VO2 has multiple polymorphs and VO2(M) has higher formation energy than other polymorphs, the common products of the hydrothermal synthesis are metastable VO2(A) or VO2(B).